Dickens and the daughter of the house - Schor, Hilary Margo (Cambridge studies in nineteenth-century literature and culture, 1999)
The daughter in Dickens' fiction is considered not as an emblem of tranquil domesticity and the hearth-fire, but as a bearer of cultural values - and as a potentially disruptive force. The daughter's secret inheritance, her 'portion', is to give Dickens a way of reading and writing his own culture differently.